Sistem Informasi Kebencanaan Daerah Kabupaten Bintan Berbasis Web dan MapBox API - Mochammad Rizki Romdoni; Kevin Perdana; Zulfachmi Zulfachmi; Saharudin Saharudin (Prosiding, 2022)
The complexity of disaster threats requires structuring and anticipating targeted and integrated development planning and programs, so an information system is needed that can help stakeholders to actively participate in disaster mitigation and management. In this study, a regional disaster information system (SIMKEDA) was developed which was designed to suit the phases of disaster management, namely pre-disaster, emergency response, and post-disaster. The representation of the disaster intensity is presented using a mapping platform from the Mapbox API. After being developed SIMKEDA can process data processing according to the phases of disaster management.